DINAMIKA KAMPUNG KUKUSAN: PERUBAHAN SOSIAL, EKONOMI DAN LINGKUNGAN TERKAIT KEBERADAAN UNIVERSITAS INDONESIA DI DEPOK 1987-2016 - Setiawan, Agus (UI Scholars Hub, 2025)
Kukusan Village is one of the communities directly affected by the establishment of the University of Indonesia (UI) campus in Depok. Located in the northern part of Depok's city government center, the village borders South Jakarta and serves as a connecting route between Depok and South Jakarta, frequently traversed by commuters residing in Depok but working in Jakarta. The history of Kukusan Village and the transformation of its landscape since the UI campus began operating in Depok until 2016 has not been widely documented. Yet, significant visible changes have occurred in terms of social, economic, and environmental aspects.This study aims to analyze the correlation between the changes taking place in Kukusan Village and the presence of the University of Indonesia in Depok, which has contributed to reshaping Depok from merely being a buffer zone for Jakarta into an emerging center for economic and educational activities. The research employs historical methods to uncover the development and dynamics of Kukusan Village in relation to the UI campus in Depok.The findings of this study indicate that the establishment of the University of Indonesia in Depok has triggered transformations in the social, economic, and environmental facets of Kukusan Village. In particular, many residents who previously worked as farmers or cultivators have transitioned to various new professions aligned with the needs and presence of the university.